Presence and severity of suicidal thoughts and behaviors across the eating disorder diagnostic spectrum: A pilot study. Issue 4 (9th December 2020) - Duffy, Mary E.; Siegfried, Nicole; Bass, Garrett; Joiner, Thomas E.
Abstract: Objectives: There is a dearth of research on suicidal thoughts and behaviors among eating disorder patients diagnosed with binge eating disorder (BED) or other specified feeding or eating disorder (OSFED). This pilot study evaluated presence and severity of suicidal thoughts and behaviors by eating disorder diagnosis in a transdiagnostic clinical eating disorder sample. Methods: Participants were individuals ( N  = 257; 91.1% female; 94.6% Caucasian) currently receiving eating disorder treatment for anorexia nervosa (AN), bulimia nervosa (BN), BED, or OSFED. Participants completed online measures of variables. Results: Lifetime and current presence and severity of suicidal ideation and suicide attempts were statistically similar among diagnostic groups. Conclusion: Though largely overlooked, treatment‐utilizing individuals with BED and OSFED may experience elevated rates and severity of suicidal thoughts and behaviors, like those with AN and BN. Attention to suicide‐related risk assessment and management is needed when treating individuals with eating disorders, regardless of diagnosis.